FORMS OF INDUSTRIAL CLUSTER AND INTERCORPORATE RELATIONSHIPS OF CLUSTER SUBJECTS (Marketing Journal, 2025)
This article analyzes the forms of industrial clusters and the importance of corporate relations among cluster participants, as well as their impact on economic efficiency and development. Industrial clusters can take various forms depending on the economi c conditions of countries and regions. The paper presents information about the main types of industrial clusters.
Keywords: cluster; corporation; strategy; competition; efficiency; ecology; industry; technology; cooperation; investment